Study of Poole-Frenkel Emission Current in Metal/Oxide/Semiconductor Structures Including the Correction of the Oxide Voltage and Temperature Effects on Key Parameters - Toumi, S.; Guerfi, T. (Science and Technology: Developments and Applications Vol. 7, 2025)
The development of new semiconductor devices and materials is crucial for advancing their fabrication and performance. Understanding their physical behavior and properties plays a fundamental role in modern technology. Among the most essential structures in semiconductor devices are metal/oxide/semiconductor (MOS) structures, which are key components in all semiconductor devices and integrated circuits. To gain insight into the physics governing these structures, various approaches are employed, one of which involves studying charge carrier transport mechanisms in MOS systems. Measuring current-voltage (I-V) curves provides valuable information about the properties of these structures and their fabrication process. However, recent studies have shown that I-V measurements alone are insufficient to fully characterize the physical properties of MOS structures. The influence of temperature is a crucial factor, and analyzing current-voltage (I-V) curves as a function of temperature (I-V-T) provides important insights into the interface states of the MOS structure. The electrical behavior of a MOS structure, as observed through its I-V characteristics, can be described by several transport mechanisms, including the tunneling currents (like Fowler-Nordheim current), the Schottky currents, the space charge limited currents flow and the Poole-Frenkel (PF) conduction process, which is the focus of this chapter. In this study, a systematic analysis of MOS structures, considering the effect of temperature on measured current-voltage curves is presented. The analysis focuses on the Poole-Frenkel (PF) transport process in Al/SiO2/p-type Si MOS devices within the temperature range of [303-423] K, under both accumulation and inversion modes. Trap states in the oxide layer were intentionally introduced by depositing a 20 nm TiN layer. The temperature-dependent charge carrier current was analyzed using the vertical optimization method (VOM) to simultaneously extract five key PF parameters: barrier height (\(φ\)), charge carrier density for holes and electrons (Nh/e), mobility of holes and electrons (\(μ\)h/e), relative permittivity (\(ε\)r), and oxide voltage correction (Vcorr). These parameters are extracted simultaneously using the Vertical Optimization Method (VOM). The results indicate that electron traps are deeper than hole traps, as evidenced by the temperature dependence of the barrier height in accumulation and inversion modes. The charge carrier densities (Nh, Ne) suggest that PF conduction is more significant in accumulation mode. Mobility analysis reveals that hole mobility remains relatively high up to 363 K (1010 cm2/Vs) but drops sharply at higher temperatures, whereas electron mobility remains relatively stable. The extracted relative permittivity (er) suggests that SiO2 exhibits enhanced polarization at lower temperatures. Furthermore, the oxide voltage correction (Vcorr) was analyzed to determine the temperature-dependent flat band potential values, yielding VFB0 = 2.606 V in accumulation mode and VFB0 = -2.302 V in inversion mode at T = 0 K. Additional derived parameters, including the PF potential barrier height (\(Δ\)EPF), charge carrier capture radius (rC), and energy density (Ue), were also evaluated. From the analysis, it is concluded that hole trapping and de-trapping dominate in accumulation mode, making p-type MOS structures unsuitable for technological applications due to significant PF leakage currents. In contrast, n-type MOS structures exhibit reduced PF conduction, even at high temperatures, making them more viable for practical applications. This investigation offers valuable information for the fabrication of MOS structures and their application in modern semiconductor technologies.